Perceptions, attitudes and understanding of health professionals of interprofessional practice at a selected community health centre - Luzaan Kock; Nondwe B. Mlezana; José M. Frantz (AOSIS, 2021)
Background: Despite being identified as a solution to the challenges related to healthcare service delivery, the incorporation of interprofessional practice (IPP) into clinical practice has been limited. To implement an interprofessional model of healthcare, successfully, health professionals need to have an understanding of IPP and its related content. Aim: The aim of this study was to explore and describe the health professionals' perceptions, attitudes and understanding of IPP at a selected community health centre. Setting: This study was conducted at a primary healthcare facility in the Western Cape, South Africa. Methods: Ethical clearance and permission to conduct the study was obtained from all relevant stakeholders. Four focus group discussions were conducted with health professionals at the facility. Themes, codes and categories were highlighted from the transcripts of the audiotape-recorded data. Findings: The findings suggest that health professionals do not have an understanding of IPP, and are thus unable to apply it practically. The health professionals perceived certain healthcare processes in the facility as barriers to the integration of practices. In addition, the health professionals expressed the need for interprofessional relationships, creation of opportunities for IPP, and communication to transform the current practice. Conclusion: To implement IPP into this facility, effectively, the authors of this study recommend that facility management implement campaigns for and training on, the transition to IPP, staff induction programmes and regular meetings.